Spatialization of Tree Species Diversity in the State of Minas Gerais - Araújo,Emanuel José Gomes de (2019)
ABSTRACT The state of Minas Gerais has a high ecological relevance mainly due to its forest species diversity. Understanding the spatialization of that diversity is of importance to develop environmental public policies. The hypothesis of this study is that the tree species diversity from different forest types, in the state of Minas Gerais, presents distribution with spatial dependence. Thus, the objective of this work was to prove that spatial dependence and to relate it between the forest types. Data from the project called “Forest Inventory of Minas Gerais” were used to calculate indices of Shannon, Simpson and Pielou. We used geostatistical and kriging tools to create spatial maps. As results, the mappings indicated that the state presents well-defined gradients of diversity and richness of forest species, increasing in North-South and from West-East directions. The spatial dependence and the spatialization of the tree species diversity show that the geostatistical modeling is a tool that supports the forest resource management. The maps of diversity can be used as indicators of potential areas for creating Conservation Units, establishing ecological corridors, besides supporting environmental policy development.